Sosialisasi Metode Berfikir Komputasional pada Pendidikan Dasar dan Menengah di Lingkup Sulawesi Selatan - Muhammad Niswar; Amil Ahmad Ilham; Zahir Zainuddin; Adnan Adnan; Ady Wahyudi P; Elly Warni; Iqra Aswad; Zaenab Muslimin (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2021)
Computational Thinking is a method of thinking that is very important and attractive to educators in primary and secondary schools. This can be seen from the enthusiasm of the participants in the socialization at SMK Telkom Makassar which was held by the community service team of the Department of Informatics, UNHAS. Community service activities were attended by 22 (twenty two) participants offline, by still paying attention to health protocols during the pandemic period. Socialization began with providing introductory material regarding the basic concepts of computational thinking, why it is important and how it is applied. The next socialization material is related to the introduction of Bebras, an international scale initiative to promote informatics and computational thinking through question challenges, how to challenge Bebras in 2020 and continue with a tutorial on using the Bebras challenge practice site. It is hoped that in the future more teachers will apply the concept of computational thinking. in the subject that is being taught and more and more students are taking part in computational thinking competitions held by Bebras at local, national and international levels.